Analysis of Cross-Cultural Understanding on Leadership Style: A Case Study of Thai and Indonesian Cultures on PT ‘Tomyum’ Tbk - Rayson Maylano; Tampubolon, Lamtiur Hasianna (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Companies around the world have expanded their business overseas through globalization that eases the restrictions for the movement of resources between countries. These companies who operate their businesses overseas faces challenges to help them achieve their objectives. The skill needed for these challenges is called cross-cultural understanding and if the leaders who dealt with diverse cultures fail to implement it, conflict might occur. Thus, having a good cross-cultural understanding is useful to minimize unintended conflict and applying the right cross-cultural leadership style is also necessary. PT ‘Tomyum’ Tbk. is an animal feed company based in Jakarta who employed people from Indonesia and Thailand. This research aims to find out which leadership style the company implements by using the GLOBE study’s cross-cultural leadership style and the GLOBE study’s nine cultural dimensions, also the coping mechanism that company’s leaders use to deal with the cultural differences within the company. This research is a single case research using a qualitative method with in-depth interviews conducted towards the employees of PT ‘Tomyum’ Tbk. to collect the data. The findings of this research suggest that the company is implementing the team-oriented leadership style by having good in-group collectivism values and uncertainty avoidance and lack no cultural dimensions overall. The company also has the same goal as their employees and the Thai manager also learns how to speak Bahasa Indonesia to minimize communication problems when dealing with his subordinates.